Pengaturan Hukum Lingkungan Internasional Terkait Pencemaran Udara Akibat Kebakaran Hutan dalam Perspektif Hukum Islam - Magdariza (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
In recent years, forest fires have frequently occurred in Indonesia, especially forests in Sumatra and Kalimantan. Not only that the certain impacts of forest fires have damaged the forest and land ecosystems, the emergence of thick smokes polluting the air as a direct result of forest and land fires has led to the emergence of new disasters. The accumulation of smokes did not only occur at the location of the fire, but it had spreaded throughout almost the entire island of Sumatra, Kalimantan and parts of Java. It had even reached the closest neighbouring countries. Areas in Malaysia, Singapore and Brunei Darussalam were likewise affected by the smokes. These forest fires are the cause of transboundary air pollution which is contrary to the principles of international environmental law. One of the Principles of International Environmental Law is well-known as "Sic Utere Tuo Ut Alienum Non Laedes" which dictates that a country is prohibited from carrying out or allowing activities that could harm other countries. The consequences of these violations can be the basis for holding accountable the states that have committed acts that are detrimental to other countries. Another related principles is "The Polluter Pays Principles" which determines that the one who pollutes is the one who is obligated to pay.